Reality therapy and AIDS - Wubbolding, Robert; Microtraining Associates (North Amherst, MA : Distributed by Microtraining Associates)
Using reality therapy, Robert Wubbolding helps an AIDS survivor evaluate the effectiveness of his actions as well as the attainability of his wants
Title from title screen
Keywords: Reality therapy; AIDS (Disease) -- Treatment; Psychotherapy